Rethinking period boundaries new approaches to continuity and discontinuity in modern European history and culture - George, Lucien; McGlynn, Jade (De Gruyter Oldenbourg, 2022)
Periodisation is an ever-present feature of the grammar of history-writing. As with all grammatical rules, the order it imposes can both liberate and stifle. Though few historians would consider their period boundaries as anything more than useful guidelines, heuristic artifice all too easily congeals into immovable structure, blinkering the historical gaze. Researchers of literature are, of course, challenged by similar dilemmas. Here, too, the neatness of periodisation can obscure the cultural output of awkward individuals that do not fit the right chronological corset, whilst also creating unfounded expectations of shared experience and expression.Rather than discard periodisation altogether, in this cross-disciplinary volume an international group of historians and literary scholars presents different ways in which accepted period boundaries in modern European history can be challenged and rethought. To do so, they explore unnoticed continuities, and instances of delayed cultural transfer that defy easy periodisation; adopt the perspective of social groups that standard periodisation schemes have ignored; and consider how historical actors themselves divide up history and how this can affect their actions